Handling Practices and Safety of Street-Vended Milk in and Around Addis Ababa City - Worku, Debebe; Seifu, Eyassu; Bultosa, Geremew (Current Nutrition & Food Science, 2014)
Forty five milk producers (MP) and 45 street-vendors (SV) of milk were selected randomly from three locations (Kotebe, Bishoftu and Chancho), Ethiopia and interviewed using semi-structured questionnaire. A total of 30 samples purposively selected from MP (15) and SV (15) were used for milk quality determinations. Milk producers in the study area generally followed unhygienic milking and improper milk handling practices. Average total bacterial (TBC) and coliform counts (CC) of milk from SV were 8.69 + 0.15 and 6.61 + 0.16 log10 cfu/ml and from MP the corresponding values were 6.98 + 0.15 and 4.88 + 0.16 log10 cfu/ml, respectively. TBC and CC of milk samples obtained from street-vendors were significantly (P < 0.05) higher (1.71 and 1.73 log units, respectively) than milk samples obtained from dairy farmers. Dominant microflora isolated from raw milk belonged to the genera Bacillus (11.7%), Micrococcus (8.3%), Pseudomonas (7.8%), Staphylococcus (24.4%), Streptococcus (5%) and family Enterobacteriaceae (lactose- (32.8%) and non-lactose fermentative (10%)). The results showed poor hygienic quality of milk that may pose public health hazards. This calls for milk quality and safety improvement in the study area.
Keywords: milk handling